2006
DOI: 10.1007/s11434-006-2206-x
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of silkworm selenoproteomes

Abstract: Selenium (Se) is an essential trace element in vivo. Its biological function is mainly exerted through selenoproteins. Selenocysteine (Sec), the active site of selenoproteins, is incorporated into the protein at an in-frame TGA codon under the guidance of Sec insertion sequence (SECIS) element in the 3′-untranslated region (UTR) of the gene. In this work, a method was developed and a series of programs were edited by PERL language to in silico identify selenoproteomes from the genome of domesticated silkworm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, when animals are exposed to a Se-rich environment, Se-containing proteins, rather than selenoproteins, become the major Se-accumulating proteins. In addition, bioinformatics analyses showed that silkworm (Bombyx mori) belongs to the selenoproteinless animals [35], although some selenoprotein-like genes were predicted from its genome [36]. The reason why silkworm does not have selenproteins is explained as that the silkworm lacks the components of Se-Cys biosynthesis and insertion machinery [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, when animals are exposed to a Se-rich environment, Se-containing proteins, rather than selenoproteins, become the major Se-accumulating proteins. In addition, bioinformatics analyses showed that silkworm (Bombyx mori) belongs to the selenoproteinless animals [35], although some selenoprotein-like genes were predicted from its genome [36]. The reason why silkworm does not have selenproteins is explained as that the silkworm lacks the components of Se-Cys biosynthesis and insertion machinery [35].…”
Section: Discussionmentioning
confidence: 99%